Efficacy and safety of Shenmai injection in the treatment of viral myocarditis: a systematic review and meta-analysis - Yang, Qianhe; Qin, Jie; Li, Ziyue; He, Yue; Zhou, Yabin (Frontiers in Pharmacology, 2024)
Purpose: To evaluate the efficacy and safety of Shenmai injection for the treatment of viral myocarditis (VMS) through systematic evaluation and meta-analysis.Methods: Seven databases were searched to identify randomized controlled trials that examined the use of Shenmai injection for the treatment of VMS. The databases were searched from inception to January 20, 2024. The quality of the included studies was evaluated via the Cochrane risk of bias tool (RoB 2) version 2. Data analysis was performed using Review Manager 5.4 and Stata 16. Results: In total, 18 randomized controlled trials were included. The trials were conducted in 2006-2024 and included 1661 patients with VMS. The results reveal that Shenmai injection combined with conventional treatment was superior to conventional treatment alone in terms of the following outcomes: total effective rate [RR=1.22, 95% CI (1.16, 1.28)], CKMB [SMD=-3.33, 95% CI (-4.85, -1.81)], electrocardiogram (ECG) efficacy [RR=1.30, 95% CI (1.20, 1.40)], AST [SMD =-0.70, 95% CI (-1.28, -0.11)], LDH [SMD=-1.17, 95% CI (-1.37, -0.97], P <0.00001], CK [SMD=-1.74, 95% CI (-2.34, -1.13)], TNF-α [SMD=-1.35, 95% CI (-1.85, -0.84)], and IL-6 [SMD=-1.40, 95% CI (-1.76, -. There were no significant differences in the incidence of adverse reactions [RR=1.56, 95% CI (0.73, 3.33), P=0.25] or cTnI levels 0.11)] between the groups.Shenmai injection with conventional treatment can reduce the degree of myocardial injury in patients with VMS, weaken the inflammatory response and improve the clinical efficacy of the conventional treatment. This approach was found to be safe. However, additional high-quality studies are necessary to confirm the reliability of this treatment method.